Quality of life and illness experiences among metastatic breast cancer women undergoing chemotherapy in Beijing: a mixed methods study - Yiqiang , Guo (2017)
Metastatic breast cancer (MBC) is an incurable illness with a median survival time ranging between 2 to 4 years following diagnosis. Research to date has limited focused on Chinese MBC women’s quality of life (QoL) and illness experiences. Thus, this study aimed to explore QoL and disease experience among MBC women undergoing chemotherapy in Beijing, China. A mixed methods approach was employed in two phases, with a survey of 176 MBC women (quantitative) followed by in-depth face-to-face interviews with 20 MBC women (qualitative) at Beijing University Cancer Hospital. QoL was measured using the Chinese version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and its breast-specific module (QLQ-BR23). The DASS-21 (Depression, Anxiety, and Stress Scale-21) was used to measure the degree of depression, anxiety, and stress, whilst the coping styles were measured using the Chinese version of Brief COPE. Using purposive sampling, 36 semi-structured interviews involving 20 MBC women were conducted to explore QoL narration of illness experiences and coping strategies. Descriptive, correlation, and general linear regression (GLR) analyses of quantitative data and thematic analysis (constant comparative) of qualitative data generated the findings. Quantitative findings indicated that 63.6% of MBC women have low QoL (≤50), 52.3% have depression, 60.2% have anxiety and 36.9% have stress. GLR revealed that predictors of QoL including age (p=0.003), marital status (p=0.028), monthly income (p=0.020), physical functioning (p=0.006) and emotional functioning (p=0.037), pain (p=0.028), dyspnea (p=0.028) and appetite loss (p<0.001). All these eight predictors explained 43.7% of the global QoL. Predictors of depression include poor marriage quality, venting, self-blame and behavioral disengagement. Also, depression was negatively associated with positive reframing. All the variances determined the depression (R2) were 35.6%. Marital status, selfblame and behavioral disengagement were the predictors of anxiety and explained 25.2% variance of anxiety in MBC women. Poor marriage quality, self-blame, denial and behavioral disengagement were the predictors of stress; all those predictors accounted for 35.4% variance of stress. Three themes emerged from the qualitative data: “living with illness/ wellness uncertainty”, “illness/wellness transition experience” and ‘illness to wellness coping strategies”. This study suggests that physical and psychological wellbeing have an impact on the QoL, depression, stress, anxiety and coping among Chinese MBC women. Thus, there is a need for healthcare professionals and healthcare policy makers to plan for the appropriate supportive program and interventions to alleviate symptoms and improve QoL for MBC women.